Considerações sobre o morrer: possíveis relações com a psicanálise - Lima, Bruna Souza de (Universidade Federal de São Carlos, 2023)
This study proposes a reflection on the cultural disapproximation and denial of death, suggesting the importance of re-signifying it as an inherent and fundamental part of living. It is dedicated to understanding the relationship of the subject with death, with emphasis on the one who is about to die, dealing with the mourning experienced and the process of acceptance of an announced terminality, in addition to exploring the mechanisms and psychic processes involved. To this end, the theory of the five stages present in the work "On death and dying", written by psychiatrist Elizabeth Kübler-Ross (1981/2017), is mainly used. Each stage is explored, seeking relationships and crossings with the theoretical approach of psychoanalysis. Finally, a reflection is proposed on the possible positions and actions in the face of death.
Considerations on dying: possible relations with psychoanalysis
Keywords: Morte; Morrer; Psicanálise; Freud; Luto antecipatório; Kübler-Ross; CIENCIAS HUMANAS::PSICOLOGIA::TRATAMENTO E PREVENCAO PSICOLOGICA